Influence of Cultural Practices and Herbicide Programs for Managing Glyphosate-Resistant Palmer Amaranth in Cold-Tolerant Sorghum - R. Liu; V. Kumar; R. Perumal; T. Lambert; T. Ostmeyer (Kansas Agricultural Experiment Station Research Reports, 2019)
The widespread evolution of glyphosate-resistant (GR) Palmer amaranth (Amaranthus palmeriS. Wats) has become a serious management concern for grain sorghum producers in western Kansas. To develop an integrated weed management (IWM) system, a field study was conducted at the Kansas State University Agricultural Research Center (KSU-ARC) in Hays, KS, in 2018, to evaluate the effect of sorghum hybrid, row spacing, and herbicide programs on GR Palmer amaranth control, shoot dry weight reduction, and sorghum grain yield. Treatments included two cold-tolerant grain sorghum hybrids: Pioneer 87P06 (commercial check) and ATx645/ ARCH12012R (developed by the KSU-ARC breeding program); row spacing of 15-in. (narrow) and 30-in. (standard); and three herbicide programs: 1) a preemergence (PRE) application of Degree Xtra at 2.5 qt/a, 2) PRE applied Degree Xtra at 2.5 qt/a followed by (fb) a sequential postemergence (POST) application of Huskie at 15 fl oz/a, and 3) a nontreated weedy check. The experiment was conducted in a randomized complete block design with a factorial arrangement of treatments and 3 replications. Sorghum hybrids were planted on April 17, 2018, in no-till wheat stubble using a seeding rate of approximately 69,696 seeds per acre. Plots were uniformly infested with a GR Palmer amaranth population prior to sorghum planting. Results indicated that both PRE alone and PREfbPOST programs provided an excellent, season-long control (>97%) of GR Palmer amaranth. In nontreated weedy plots, GR Palmer amaranth density was not affected by sorghum hybrid or row spacing; however, its shoot dry weight was reduced by 37% with 15-in. compared to 30-in. rows. Sorghum grain yield of Pioneer 87P06 was increased by 27% in 15-in. compared to 30-in. rows; whereas, row spacing had no effect on grain yield of ATx645/ARCH12012R hybrid. These preliminary results suggest that combination of narrow row spacing (15-in.) and PRE application of Degree Xtra can potentially be utilized for effective and season-long control of GR Palmer amaranth in early-planted (cold-tolerant) grain sorghum.
Keywords: cold-tolerant grain sorghum; Palmer amaranth; row spacing; sorghum hybrid